PENGARUH KOMPETENSI DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT. SURYA MADISTRINDO DI SURABAYA - Susetyorini, Susetyorini; Rahman, Abdul (Fakultas Ekonomi Universitas Gresik, 2018)
This study aims To determine the competence and career development have an effect on the performance of employees performed in PT Surya Madistrindo is a business unit engaged in the field of Sales and Field Marketing Gudang Garam (GG) brand that is currently growing rapidly in Indonesia and various countries in the world of companies Is committed to provide the best service for the best customer to the customer, given the service is the main activity in Sales and Field Marketing, therefore needed a reliable and qualified human resources. In this research, the type of data used is primary and secondary data. The data collection techniques used are koesioner, interview and observation. Method of analyzing the data used is quantitative quantitative methods obtained from the results of respondentsÃƒÆ’Ã‚Â¢ÃƒÂ¢Ã¢â‚¬Å¡Ã‚Â¬ÃƒÂ¢Ã¢â‚¬Å¾Ã‚Â¢ answers to the questionnaire. Then after analyzing the data need to be tested instruments so that the data obtained can be tested and reliable The result of this research shows F count> F table (34,639> 3,085), thus H0 is rejected and H1 accepted, it indicates that jointly competence and career development variables have an effect on employee performance which is dependent variable on employee PT. Surya Madistrindo Surabaya. While the competence variable (X1) on employee performance (Y) shows t count> t table (4.570> 1,983) then H0 is rejected and H1 accepted, this indicates that competence significantly influence employee performance, career development (X2) on employee performance ) Shows t count = 4.760 means t count> t table (4,760> 1,983), m0unjukkan H0 rejected and H1 accepted which means career development has a significant effect on employee performance.ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475727